Report & accounts of Bangladesh Rehabilitation Assistance Committee for the period from 1 February 1973 to 31 January 1974 - BRAC (© BRAC, 2016)
This Financial Statement prepared by S.F. Ahmed & Co. Chartered Accountants, 95 Motijheel, Dacca, Bangladesh.